Internalising Religious Moderation Through Historical Memory - Wahyudi, Johan; Madjid, M. Dien; Fahmi, Kaula (The International Journal of Pegon : Islam Nusantara civilization, 2024)
This study aims to describe a historical perspective on religious moderation in the South Sulawesi region, focusing on the harmonious relationship between the Toraja, Bugis and other tribes. Although the majority of Tana Toraja's population is Christian, good relations with people of other religions, including Islam, have been established and maintained for centuries. Through a historical approach, this research will seek the historical roots of tolerance and peaceful relations between religious groups in the region. The history of the South Sulawesi region shows a tradition of religious moderation that has been passed down from generation to generation. The religious and cultural diversity of the region has shaped a unique and complementary social identity, despite the dark historical memories that exist between them. The research method used in this study is oral source-based historical analysis with Toraja traditional leaders. The data collected will be analysed to reveal the pattern of relationship between the tribes in the context of religion. The results of this study will illustrate that religious tolerance in South Sulawesi has been rooted since the past and did not appear out of nowhere. The tradition and culture of religious moderation have played a role in creating a social environment that respects differences and facilitates interfaith dialogue. Penelitian ini bertujuan untuk mendeskripsikan perspektif sejarah moderasi beragama di wilayah Sulawesi Selatan, dengan fokus pada hubungan harmonis antara suku Toraja, Bugis, dan suku lainnya. Meski mayoritas penduduk Tana Toraja beragama Kristen, namun hubungan baik dengan pemeluk agama lain, termasuk Islam, telah terjalin dan terpelihara selama berabad-abad. Melalui pendekatan historis, penelitian ini akan mencari akar sejarah toleransi dan hubungan damai antar kelompok agama di wilayah tersebut. Sejarah daerah Sulawesi Selatan menunjukkan tradisi moderasi beragama yang diwariskan secara turun temurun. Keberagaman agama dan budaya di wilayah tersebut telah membentuk identitas sosial yang unik dan saling melengkapi, meskipun ada kenangan sejarah kelam yang ada di antara mereka. Metode penelitian yang digunakan dalam penelitian ini adalah analisis sejarah berbasis sumber lisan dengan tokoh adat Toraja. Data yang terkumpul akan dianalisis untuk mengungkap pola hubungan antar suku dalam konteks agama. Hasil penelitian ini akan memberikan gambaran bahwa toleransi beragama di Sulawesi Selatan telah mengakar sejak dahulu kala dan tidak muncul begitu saja. Tradisi dan budaya moderasi beragama berperan dalam menciptakan lingkungan sosial yang menghargai perbedaan dan memfasilitasi dialog antaragama.